Potential for soybean rust tolerance among elite soybean lines in Uganda - Oloka, Herbert K.; Tukamuhabwa, P.; Sengooba, T.; Adipala, E.; Kabayi, P. (Crop protection, 2009)
Soybean rust, (Phakopsora pachyrhizi), currently the most devastating disease of soybeans worldwide, is known to challenge single resistance genes deployed against it and therefore, disease tolerance is indisputably the most viable measure in controlling the pathogen. Studies were conducted at Namulonge in Central Uganda to assess the level of tolerance to soybean rust among selected elite soybean lines. Seven elite lines together with three local checks were tested in a split-plot design where some plots were protected with fungicide to estimate the level of tolerance to soybean rust. The experimentwas conducted for three cropping seasons beginning second rains of 2005. A rust tolerance index (RTI) was computed for each test line as the ratio of yield from unprotected plots to yield from protected plots. The study showed that high levels of tolerance to soybean rust were present in the test lines. The soybean lines that showed high levels of tolerance included MNG 10.3 and MNG 3.26 all showing RTIs higher than 0.93. These lines also out-yielded the local checks by about 400 kg ha 1 and are recommended for multi-location testing.
Keywords: Lines; Rust tolerance index; Resistance; Phakopsora pachyrhizi; Yield